4‐Hydroxy Enigmol, a 1‐Deoxyphytosphingolipid that Exhibit Good Activity against Prostate and Colon Cancer. Issue 5 (2nd February 2023) - Kaur, Parleen; Sharma, Sonia; Goel, Akshita; Sharma, Purshotam; Agnihotri, Navneet; Kaur, Ramandeep; Singh, Vasundhara
Abstract: In the present work, 4‐hydroxy enigmol (1 ), an analogue of enigmol which is a known orally bioavailable 1‐deoxysphingolipid, effective against multiple cancer cell lines, has been synthesized with an additional hydroxy group for improved anti‐cancer activity. The additional group in compound (1 ) is likely to show enhanced activity due to improved cell permeability and hydrophilicity. The key steps involved are stereoselective cross metathesis reaction and OsO4 /NMO mediated dihydroxylation. Further, analogues of 4‐hydroxy enigmol (1 ) with varying chain lengths (2, 3 ) have also been synthesized using the same synthetic strategy for varying hydrophobicity as an additional structural feature. To support the genesis in the design of compound (1 –3 ), the pharmacokinetic studies and docking analysis has been done for calculating the polar surface area, binding affinity and hydrophobicity/hydrophilicity. The preliminary in‐vitro cytotoxicity on cancer cell lines displayed promising activity against the PC‐3 cell lines and HCT‐116 cell lines. Abstract : A concise synthesis of 4‐Hydroxy enigmol and its chain analogues (1 –3 ) with good overall yield via a simple route have been done with cross metathesis reaction and OsO4 /NMO mediated dihydroxylation as the key steps with feasible reaction conditions. The in silico analysis depicted good binding affinity of the analogues with the Sphingosine Kinase I protein whose inhibition is a proposed mechanism for the apoptosis leading to anti‐cancer activity. Furthermore, molecular dynamics simulations were also performed to assess the stability of SPHK1‐Compounds complex. The in vitro analysis have been done on PC‐3 cell lines and HC116 cell lines in which all three compounds (1 –3 ) showed good anti‐cancer activity with compound (1 ) showing the best activity with IC50 0.0039 μm on PC‐3 cell lines and 0.0008 μm on HCT‐116 cell lines.